Primary amelanotic malignant melanoma of the esophagus: a case report - Naomichi Koga; Nobuhide Kubo; Hiroshi Saeki; Shun Sasaki; Tomoko Jogo; Kosuke Hirose; Yuichiro Nakashima; Eiji Oki; Yutaka Koga; Yoshinao Oda; Hisao Oiwa; Toshio Oiwa; et al. (Surgical Case Reports, 2019)
Abstract Background Primary amelanotic malignant melanoma of esophagus, which is a subtype of primary malignant melanoma of the esophagus (PMME), is a very rare disease with a poor prognosis. We herein report a case of the amelanotic type of PMME. Case presentation An 86-year-old woman was admitted to our hospital with symptoms of dysphagia. An endoscopic examination and constructed radiography revealed an elevated and semipedunculated lesion with an ulcer in the lower thoracic esophagus accompanied by another submucosal lesion of the esophagus. She was diagnosed with esophageal squamous cell carcinoma by a preoperative endoscopic biopsy. We performed thoracoscopy- and laparoscopy-assisted subtotal esophagectomy with lymphadenectomy. Based on the surgical specimens, although there were no melanocytes, we made a diagnosis of a malignant melanoma immunohistochemically; the tumor cells were positive for S-100 protein and HMB45 focally and partially for Melan-A. Conclusion We experienced a case of primary amelanotic malignant melanoma, and the patient has remained disease-free for 1 year since the surgery. Since the diagnosis of amelanotic type of PMME is difficult, it should be made by the combination of a morphological examination, pathological examination, and immunohistochemistry.